Income elasticity of food expenditure among urban households in Sulawesi: Evidence from engel’s law - Siti Nurhaliza; Mohamad Ichwan; Rita Yunus; Edhi Taqwa; Yunus Sading (Privietlab, 2026)
This study examines the responsiveness of food expenditure shares to income changes among urban households in Sulawesi using income elasticity analysis. Employing cross-sectional microdata from the 2023 National Socio-Economic Survey (SUSENAS), comprising 13,933 urban households across six Sulawesi provinces, we calculate arc elasticity for nine income group transitions. The results reveal predominantly negative elasticity values ranging from -0.008 to -0.504, confirming patterns consistent with Engel’s Law. The elasticity pattern exhibits an inverted-curve shape: weak in low-income groups (-0.0103 to -0.091), strengthening in middle-income groups (-0.2 to -0.5), and moderating in the highest transition (-0.059 to -0.268). This reflects critical threshold effects, where middle-income households demonstrate the strongest responsiveness in reallocating expenditures from food to non-food categories. Substantial interprovincial variations emerged, with Gorontalo exhibiting the strongest elasticity (-0.504), while Central Sulawesi showed unique patterns, including positive elasticity at specific transitions. Elasticity values consistently below one confirm food as a necessary good across all provinces. These findings provide crucial policy insights: low-income households require targeted protection through subsidies and social assistance, whereas middle-income households would benefit most from income growth policies. Provincial heterogeneity underscores the need for context-specific rather than uniform regional interventions.